3D skull modelling and description of a new baurusuchid (Crocodyliformes, Mesoeucrocodylia) from the Late Cretaceous (Bauru Basin) of Brazil. Issue 3 (18th April 2021) - Darlim, Gustavo; Montefeltro, Felipe C.; Langer, Max C.
Abstract: Baurusuchidae is one of the most diverse groups of South American notosuchians, unambiguously recorded in Late Cretaceous deposits of Brazil and Argentina. The group is characterized by a reduced tooth formula, a lateromedially compressed rostrum, and a verticalized quadrate, representing one of the top predators of their faunas. Historically, skull morphology is the most employed tool to investigate the relationships of baurusuchids, as most of the species have been primarily based on cranial remains. The present study describes a new baurusuchid species from the Bauru Basin of Brazil, based on the first tridimensional digital reconstruction of individualized skull bones for Notosuchia, and discusses its phylogenetic position within the group. The new species differs from all the other known baurusuchids by a depression on the posterior portion of the nasal bearing a crest, an infraorbital crest of the jugal that extends until the anterior margin of the lacrimal, the dorsal surface of the frontal lacking a longitudinal crest or depression, and the lateral convexity of the squamosal prongs participating in the occipital wall. The new taxon is consistently positioned as sister to the remaining baurusuchines, with Aplestosuchus sordidus and Stratiotosuchus maxhechti, as successive sister‐taxa to a monophyletic Baurusuchus ( Ba. albertoi, Ba. Salgadoensis, and Ba. pachecoi ). Our updated phylogenetic analysis helps to differentiate the two major Baurusuchidae lineages, Baurusuchinae and Pissarrachampsinae. Yet, the new species shares morphological features with both groups, suggesting the occurrence of "Zones of Variability" in the radiation of Baurusuchidae. Abstract : Baurusuchidae is a group of terrestrial Crocodyliformes from the late Cretaceous of South America. In the present study, we propose a new species and provide the first detailed description based on 3D reconstructions for each skull bone. Our updated phylogenetic analysis helps to differentiate the two major Baurusuchidae lineages. Yet, the new species shares morphological features with both groups, suggesting the occurrence of "Zones of Variability" in the radiation of Baurusuchidae.